1988
DOI: 10.1038/icb.1988.50
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of immature lymphoid cells in human umbilical cord blood

Abstract: SummaryThe antigenic phenotype of neonatal lymphoid cells isolated from umbilical cord blood was investigated using monoclonal antibodies and flow cytometry. Although the majority ofcells expressed mature T or B cell differentiation antigens, small subpopulations of phenotypically immature lymphocytes were detected. A small proportion (mean 2-8%) ofcells expressed the common acute lymphoblastic leukaemia antigen (CD-10), a significantly higher figure than that detected on adult peripheral blood lymphocytes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
3
5
1
Order By: Relevance
“…Furthermore, data derived from analysis of cord blood ob tained at term or premature delivery may have been affected by the stress of delivery or the underlying reason for premature birth, such as infection or hypoxia [9-1 1 ]. Addition ally, most previous studies have used tech niques to enumerate lymphocytes that may result in inaccurate estimations or selective loss of cellular populations [9][10][11][12][13]. Two stud ies which used direct whole blood staining techniques to examine T lymphocyte subpop ulations in large numbers of patients at 18-20 weeks and at term, respectively, demon strated results consistent with the data of the present study [8.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, data derived from analysis of cord blood ob tained at term or premature delivery may have been affected by the stress of delivery or the underlying reason for premature birth, such as infection or hypoxia [9-1 1 ]. Addition ally, most previous studies have used tech niques to enumerate lymphocytes that may result in inaccurate estimations or selective loss of cellular populations [9][10][11][12][13]. Two stud ies which used direct whole blood staining techniques to examine T lymphocyte subpop ulations in large numbers of patients at 18-20 weeks and at term, respectively, demon strated results consistent with the data of the present study [8.…”
Section: Discussionsupporting
confidence: 82%
“…Cord blood totals and differentials for neonates of infeeted mothers did not differ appreciably from literature values [22]. Our results with cord blood T-eell CD4 • and CDS ' subsets from seven neonates of Infected mothers apparently eontlict with most [27][28][29][30][31][32], but not all [33], studies on this topic. Generally, the CDS ' pereentage is ritthcr low in CBMC.…”
Section: Discussionsupporting
confidence: 52%
“…The variable number of contaminating immature nonlymphoid mononuclear cells remaining in cord cell suspensions after Ficoll may account for these differences. In our study, as in that of Bradstock (1988), the use of a flow cytometer may make it possible to select a small lymphoid window, thereby eliminating nonlymphoid cells.…”
Section: Previous Investigators Have Reported Conflicting Resultsmentioning
confidence: 76%
“…(Bradstock et al, 1988) found, or significantly lower (Deacock et al, 1992;Foa et al, 1984;Hannet et al, 1992). The variable number of contaminating immature nonlymphoid mononuclear cells remaining in cord cell suspensions after Ficoll may account for these differences.…”
Section: Previous Investigators Have Reported Conflicting Resultsmentioning
confidence: 97%